1995
DOI: 10.1063/1.870966
|View full text |Cite
|
Sign up to set email alerts
|

Drift-wave-like density fluctuations in the Advanced Toroidal Facility (ATF) torsatron

Abstract: Density fluctuations in low-collisionality, low-beta (p-O.1 %), currentless plasmas produced with electron cyclotron heating (ECH) in the Advanced Toroidal Facility (ATF) torsatron [Fusion Technol. 10, 179 (1986)] have been studied using a 2 mm microwave scattering diagnostic. Pulsed gas puffing is used to produce transient steepening of the density profile from its typically flat shape; this leads to growth in the density fluctuations when the temperature and density gradients both point in the same direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This is consistent with the result of linear calculation of core turbulence, which shows that the most dominant instability is ITG. This is in clear contrast to the turbulence characteristics of ECRH plasma of ATF [51,52] and ECRH + NBI plasma of Heliotron-E [53]. The core fluctuation in both devices increases with increase of electron density gradient.…”
Section: Turbulence Characteristics From the Driving Term And Tempora...mentioning
confidence: 61%
“…This is consistent with the result of linear calculation of core turbulence, which shows that the most dominant instability is ITG. This is in clear contrast to the turbulence characteristics of ECRH plasma of ATF [51,52] and ECRH + NBI plasma of Heliotron-E [53]. The core fluctuation in both devices increases with increase of electron density gradient.…”
Section: Turbulence Characteristics From the Driving Term And Tempora...mentioning
confidence: 61%
“…In ATF, of which magnetic configuration is similar to LHD, it was reported that measured core turbulence was dissipative trapped electron mode (DTEM) [29]. The linear growth rate of DTEM increase with increase of collisionality.…”
Section: Fig 16 Profiles In D Plasma (A-1)~(a-5) and H Plasma (B-1)~(...mentioning
confidence: 99%
“…Linear 3D gyrokinetic calculations [7,8] have predicted that the anomalous electron thermal transport in the HSX stellarator may be caused by trapped-electron mode drift wave turbulence. While significant effort has been made to study the ion temperature-gradientdriven (ITG) [9], and trapped electron modes (TEM) [10] in conventional stellarator/heliotron configurations, theoretical and experimental studies on turbulence-induced transport for stellarators with quasi-symmetry will provide important new contributions to the goal of future fusion reactor development.…”
Section: Introductionmentioning
confidence: 99%